Perancangan Sistem Informasi Pengolahan Data Produksi TBS (Tandan Buah Segar) Kelapa Sawit Berbasis Material Requirement Planning Pada PT. Tanjung Jaya Lestari Lampung Tengah - Zohan Fanani; Wiwin Susanty (Universitas Bandar Lampung (UBL), 2013)
Analysis of Data Processing System Analysis Method to determine the production data processing FFB (fresh fruit bunches) Oil Palm at PT. Tanjung Jaya Lestari presented in this thesis. This analysis is an attempt to facilitate the ability to run the system using a variety of systems and one of them is Data Processing System Production at PT. Tanjung Jaya Lestari.